2005
DOI: 10.1081/dis-200040137
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ethylene Glycol on the Thermodynamic and Micellar Properties of Tween 40, 60, and 80

Abstract: The self-aggregation of Tween 40, Tween 60, and Tween 80 in ethylene glycol-water mixture was investigated using surface tension, density, and fluorescence measurements. The mixtures were observed to appreciably affect the critical micelle concentration (cmc) of the surfactants and their aggregation numbers. In order to evaluate the influence of the solvent mixture, the difference in the Gibbs energy of micellization of Tween 40, Tween 60, and Tween 80 between water and binary mixtures were determined. The abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 23 publications
2
39
0
Order By: Relevance
“…1. The CMC values read from the curves for pure surfactants agree reasonably well with literature values [1,19,[34][35][36].…”
Section: Critical Micelle Concentrationsupporting
confidence: 70%
“…1. The CMC values read from the curves for pure surfactants agree reasonably well with literature values [1,19,[34][35][36].…”
Section: Critical Micelle Concentrationsupporting
confidence: 70%
“…From these investigations, the solution behaviour of these substances and their structural characteristics are reasonably well known. In recent years, however, many workers have turned their attention to the aggregation phenomenon of surfactants in solvent systems constituted by a mixture of water with some polar organic solvent [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. In these studies, water is gradually replaced with other polar solvent, so that one can explore a wide range of solvophobicities.…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that mixing of EG (or TEG) with water modified the curvature of the interface and produced the phase transformation at a lower value of cosurfactant, thereby increasing the solubilization capacity of the system. The minimum in the X b vs ψ profile can be explained as a competition between two opposing factors; it has been reported that mixing of EG with water increased the cmc of both ionic and nonionic surfactant solutions [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. On the other hand, since the EG-hydrocarbon interfacial tension is smaller than the water interfacial tension, the aggregation number in the mixed solvent decreased, which in turn would increase the surface area per surfactant molecule.…”
Section: Isothermal Phase Behavior Of Brij-76/bu/i-oc/water Brij-76/mentioning
confidence: 98%
“…EG is an important member of this class of organic NPS, since it contains two hydroxyl groups that can undergo hydrogen bond formation, a prerequisite for the aggregation of surfactants in a solvent [22]. But only limited studies have been carried out on the formation and characterization of micelles using this NPS [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. It has been reported that both inter-and intramolecular hydrogen bonds are formed in EG, although they are not as strong as those formed in water.…”
Section: Introductionmentioning
confidence: 99%